Deletion series in the P1 protein of the Sweet potato mild mottle virus identifies the shortest fully functional RNA silencing suppressor domain - Szabó, Edit Zsuzsanna; Kemény, Lajos; Lakatos, Lóránt (Acta Biologica Szegediensis, 2014)
RNA silencing is a part of the plant innate immune system that could effectively cope with intruders, like viruses. However, viruses evolved proteins that can suppress RNA silencing thus supporting virus spreading in the host. To counteract RNA silencing, suppressor proteins attack different players of RNA silencing pathway. The P1 protein of the Sweet potato mild mottle virus binds and inactivates small RNA loaded RISC complexes. Using a deletion series in the P1 protein we aimed to identify the possible smallest working version of P1. Our results revealed that the minimal RNA silencing suppressor domain of P1 is as small as 210 amino acids in size.